Pengaruh Model Pembelajaran Langsung Berbasis Praktikum Terhadap Keterampilan Proses Sains dan Kemampuan Berpikir Kritis Siswa - Royani, Ida; Mirawati, Baiq; Jannah, Husnul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aims to determine the effect of practicum-based direct learning model on science process skills and students' critical thinking skills. This study is a quasi-experimental research with the Pretest-posttest Control Group Design. The sampling technique using Cluster Random Sampling. The sample in this study were students of class XI IPA 1 (18 students) as the experimental class and class XI IPA 2 (18 students) as the control class in AL-Hamzar High School Tembeng Putik. The research instruments used were learning implementation observation sheets, the science process skills observation sheets, and learning achievements tests. The data obtained were analyzed using the t test with the help of SPSS 16. The results of data analysis showed that the implementation of learning in the first meeting reached 81% and the second meeting 96% with a very good category. The students’ science process skills in both classes show that students' science process skills varies. The students’ critical thinking ability in the experimental class was higher than the control class. The results of pretest data analysis showed that students' critical thinking ability in the experimental class was 35.5 while the control class was 49.5. Students' critical thinking ability in post-test increased in the experimental class to 73.5 while the control class was 58.6. The results of the t-test show that tcount > ttable (3.45 > 2.04) so it can be concluded that the practicum-based direct learning model was affect toward students' science process skills and critical thinking ability.